Pharmacovigilance Bibliometrics: Visualizing Thematic Development in the Category of Pharmacology and Pharmacy in Web of Science - Wang, Li; Feng, Wanyu; Duan, Jingli; Liang, Jun (Frontiers in Pharmacology, 2021)
Introduction: Pharmacovigilance studies include monitoring and preventing the occurrence of new, rare, or serious adverse drug reactions, making it possible to discover new safety issues without delay. Bibliometrics could assist scholars to analyze the development of pharmacovigilance. Methods: The MeSH terms of both pharmacovigilance and “adverse drug reaction reporting system” were retrieved in the Science Citation Index Expanded. The articles from 1974 to July 2021 in the pharmacology and pharmacy category were recruited. The citation reports including the publication numbers, h-index, and sum and average cited times in terms of annuals, countries, organizations, authors and journals were tabulated. The coauthorship relations in the analysis units of countries, organizations, and authors; the top 10 burst references; the document citation network; and the author’s keywords co-occurrence overlay map were visualized by bibliometric software including the website (https://bibliometric.com/), VOSviewer, CiteSpace, and CitNetExplorer. Results: From 1974 to the present, the most high-yield publication year, country, institute, author, and journal were 2020 (n = 222), France (n = 522), Netherlands Pharmacovigilance Centre Lareb (n = 82), Jean–Louis Montastruc (n = 125), Drug Safety (n = 384), respectively, in all 2,128 articles. Similarly, the United States, Institut National de la Sante et de la Recherche Medicale, and Jean–Louis Montastruc had the most coauthorship strength at the macrolevel (global), mesolevel (local), and microlevel (individual). The topics of burst references covered are the development of methodology, issues of patients reporting and under-reporting, evaluation of methods and databases, assessment of causality, and perspectives in pharmacovigilance. Eight clusters were grouped in the document citation network. “Pharmacovigilance,” “adverse drug reactions,” “pharmacoepidemiology,” “drug safety,” and “signal detection” were the research priorities, while “drug-related side effects and adverse reactions,” “VigiBase,” “disproportionality analysis,” “social media,” “FAERS,” “chemotherapy,” “patient safety,” “reporting odds ratio,” and “preventability” might be the future research hotspots. Conclusion: Positive synergies can be observed in this study by employing the multiple software tools which established the relationship between the units of analysis. The bibliometric analysis can organize the thematic development and guide the hotspots of pharmacovigilance in pharmacology and pharmacy.